Peran Pesantren dalam Mengawal Rantai Pasok Halal di Indonesia - Hajar Hajar (Universitas Islam Raden Rahmat, 2023)
This study aims to describe the role of Islamic boarding schools in overseeing the halal supply chain in Indonesia. The research design uses a qualitative descriptive method with a phenomenological approach obtained from secondary data from the literature, journals, books and other relevant sources. The findings of this study indicate that pesantren has recently experienced significant developments, especially in terms of participating in economic empowerment and independence. This can be seen from the number of pesantren, both salaf, modern and semi-modern, which have begun to incorporate entrepreneurship curricula and carry out production activities and other types of business. This phenomenon proves that pesantren has a strategic role in overseeing the halal supply chain in Indonesia. There are two things that Islamic boarding schools can do in overseeing the halal supply chain: educate the public about the criteria for halal and haram ingredients. Second, conducting various business activities such as food and beverage production.